How media pluralism navigates ideological orientations: the case of Slovenia - Valič, Tamara Besednjak; Rončević, Borut; Tomšič, Matevž (Frontiers in Communication, 2023)
Media and its reporting shape public opinion, and doing this can obtain an indirect and significant influence on the course and results of the political process. In this context, media operates as an active element of the political space. Within this paper, the authors deal with the current state of media pluralism in Slovenia. In doing so, the authors discover weak media plurality as the main characteristic of the Slovenian media space. The authors use the Janis-Fadner coefficient of imbalance to analyze a total of 1434 media texts published in 10 different Slovenian media outlets. The results show the existence of a distinct media landscape where the majority of media reporting is strongly anti-right-wing-governmental and left-wing oriented.